ANALISIS SPASIAL DEBIT PUNCAK DAERAH ALIRAN SUNGAI BERINGIN DENGAN METODE RASIONAL - Rifqi, Putra Muhammad; Setyowati, Dewi Liesnoor; Suroso, Suroso (Geo-Image, 2017)
This study aims to 1). Calculating peak discharge of BeringinWatershedby usingRational methode; 2.) Spatially Analyzingof peak discharge in Beringin Watershed.Peak discharge ( Qp ) calculated with the Rational methode Qp = 0,00278 .C .I .A using map overlay technique. Spatial technique analysis used to get the spatial information related to scatter peak discharge culmination of the condition of those three variable, namely the surface run off coefficients depend with human activity, value of the rain fall intensity and catchment area of every sub-watershed to the total discharge of Beringin Watershed.This research produce the top Beringin Watershed Qp amount 25,5 m3/swith five peak discharge of sub-watershed areasBeringin Watershed the highest peak discharge to the lowest successive, namely Demangan sub-watershed, Tikungsub-watershed, Dondong sub-watershed, Beringin hilir sub-watershed, and Gondoriyo sub-watershed with the each value is 10,8 m3/s (42,3 % ), 9,5 m3/s (37,3 %), 2,4 m3/s (9,4 %), 2,2 m3/s ( 8,6 %), and 0,6 m3/s (2,4%).The different condition of peak discharge Beringin Watershed spatial distribution may cause of somethings, as characteristic variation of run off coefficient value, total rainfall intencity that come in to the watersheed, and areas on each sub-watershed.